PENAMBAHAN MINYAK ATSIRI RIMPANG LENGKUAS MERAH PADA EDIBLE COATING TAPIOKA TERHADAP MUTU BAKSO AYAM SELAMA PENYIMPANAN DINGIN - Nadia Novianti Tamba; Fajar Restuhadi; Raswen Efendi (Fakultas Pertanian Universitas Riau, 2022)
Chicken meatballs are perishable food because of their complete nutritional content and a suitable place for microbial growth. One of the efforts to maintain the quality of chicken meatballs is by providing an edible coating that adds antibac- terial such as red galangal essential oil. This research aimed to obtain the best concentration of essential oil in an edible coating to maintain the quality of chicken meatballs during cold storage. The research used a completely randomized design (CRD) consisting of five treatments as follows: without the addition of essential oils (P0); the concentrations of essential oils were 0.5% (P1); 0.75% (P2); 1.00% (P3); and 1.25% (P4). A sample was stored at a cold temperature (5ºC) for 0, 5, 10, and 15 days. The data obtained were analyzed statistically using Analysis of Variance (ANOVA), then analyzed with the Duncan᾽s Multiple Range Test (DMRT) at the 5% level. The results showed that edible coating added with red galangal essential oil had a significant effect on water content, pH, total plate count (TPC), descriptive sensory assessment on chicken meatballs. The best treatment was edible coating tapioca with red galangal essential oil concentration of 1%, which can maintain quality up to the 10th day of storage with a water content was 64.55%, acidity value (pH) was 6.26, TPC value was 4.94 log CFU/ml, and sensory assessment descriptive for color 3.47 (bone), flavor 3.20 (chicken flavor), texture (chewy).